Paul and the Rhetoric of Resurrection : 1 Corinthians 15 as Insinuatio - Christian, Timothy J. (Biblical Interpretation Series, 2023)
Have you ever wondered why Paul leaves the resurrection discussion in 1 Corinthians 15 for the end of the letter? Have you pondered how 1 Corinthians 15 functions as the climax to 1 Corinthians? This book answers those questions by exploring insinuatio , the Greco-Roman rhetorical convention used to address prejudiced or controversial topics-like resurrection-at the end of a discourse. This is the most thorough treatment of insinuatio in Biblical and Classical studies to date. It examines the Greco-Roman rhetorical handbooks and speeches on insinuatio , compares them to what Paul does in 1 Corinthians 15, and finds that this was precisely Paul's rhetorical strategy in 1 Corinthians.